2022
DOI: 10.2166/wh.2022.267
|View full text |Cite
|
Sign up to set email alerts
|

Identification and assessment of antimicrobial resistance bacteria in a hemodialysis water treatment system

Abstract: The water treatment process is a vital factor for hemodialysis (HD) patients. This study aimed to assess the degree of contamination of HD water by bacteria at the HD center of Mohammedia, Morocco, in addition to evaluating the antimicrobial resistance of isolated bacteria. Fifty-four water samples were taken, the appropriate cultures were used to isolate the pathogenic bacteria, which were identified biochemically and molecularly by 16S RNA sequencing. Their susceptibility to antimicrobial drugs was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The overall prevalence of bacterial growth was reported at 61.3%(n = 38/62) indicating a high level of contamination of hospital surfaces, and equipment. The reporting of contamination on the sampled surfaces was higher than average reported contamination rates in literature [7,11,14,17,18]. A possible reason for the prevalence high contamination could be to poor adherence to hospital IPC guidelines for infection control.…”
Section: Discussion Of Findingsmentioning
confidence: 72%
See 2 more Smart Citations
“…The overall prevalence of bacterial growth was reported at 61.3%(n = 38/62) indicating a high level of contamination of hospital surfaces, and equipment. The reporting of contamination on the sampled surfaces was higher than average reported contamination rates in literature [7,11,14,17,18]. A possible reason for the prevalence high contamination could be to poor adherence to hospital IPC guidelines for infection control.…”
Section: Discussion Of Findingsmentioning
confidence: 72%
“…The most prevalent genus in terms of frequency levels in the facility was as follows: Acinetobacter 19 (41.3%) followed by Enterobacter 6 (13.0%) which were predominantly surface contaminants and also gram-positive Staphylococcus 6 (13.0%) mainly found on humans. Studies in Morocco and Rwanda had similar ndings on the isolates though had a variable frequency of distribution [9,14]. Whereas the high contamination level with Acinetobacter species may be justi ed by the community being mainly agricultural -wince Acinetobacter is a soil inhabitant -the main concern is the fact that Acinetobacter baumanii is notorious in causing hospital associated pneumonia, septicemia, meningitis, UTIs and other infections, similar to Kleibsiella [32,33].…”
Section: Conclusion and Recommendationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Evaluation of water used in HD continues to be a requirement, looking at the quantity of organisms in water as well as the type of organisms isolated. A study in Morocco 22 identified that even though 51/54 tested samples passed national and European standards for final dialysate quality (heterotrophic plate counts of <100 CFU/mL, absence of coliforms in 100 mL, endotoxin level of <0.25 EU/mL), 50% of the samples collected after carbon filtration showed positive cultures, including Pseudomonas spp ( N = 12), Stenotrophomonas maltophilia ( N = 16), and Burkholderia cepacia ( N = 4). In addition, 43.75 % were MDR and 18.75% were extensively drug-resistant.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Microbiological contaminants can also be found in water, and their presence is often associated with failures of the dialysis water treatment and distribution system (Ferreira et al 2015;Ferreira et al 2020). Among the most frequent, gram-negative bacteria (Okunola and Olaitan, 2016;Anversa et al, 2022;Chaoui et al, 2022), that may be associated with infections in hemodialysis patients (Tejera et al, 2016;Thet et al, 2019), can be highlighted. These bacteria can also represent a serious threat to patients due to their ability to form biofilms and develop antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%